Selective attention of elite versus youth biathletes in rest and after physical load - Birklbauer, J.; Dirnberger, J.; Buchecker, M.; Sattlecker, G.; Finkenzeller, T.; Kösters, A.; Wiesinger, H. P. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Attention abilities are critically important for performance in self-paced and far-aiming sports, enabling athletes to focus on targets and resist distractions. Accordingly, elites in shooting and archery showed better selective attention compared to their lower-level counterparts (1). In biathlon, demands on attention are arguably even greater, as shooting has to be completed under time constraints and significant physical exertion. First indications of enhanced conflict control in biathletes with superior shooting performance were derived from cluster analyses (2). Based on these preliminary findings, we hypothesized that elite outperform youth biathletes in visual interference control of attention during rest and even more after physical exertion. METHODS: Twenty-six youth biathletes (14 males; 15.4±1.1 yrs of age) and 14 European and World Cup biathletes (10 males; 22.7±3.1 yrs) fired 3 x 5 shots in prone and standing shooting positions without physical load followed by 2 x 5 shots in both positions during a simulated pursuit race. According to their usual race distance, elites had to roller ski 5 loops of 2.5 km and youth 5 loops of 1.5 km in their individual race pace. Selective attention was assessed using a modified Eriksen-Flanker Task both before the rest condition and after the simulated competition. 50m-shooting performance was measured on a scale from 0 to 10 rings. RESULTS: Frequentist 2-way ANOVAs revealed neither significant group differences (p>.562) nor interaction effects (p>.302) in the interference scores or incongruent trials of response times (RT) and errors with low effect sizes (*2p0.165) and strong evidence supporting a change (BFincl>11.6), RT improved from pre to post test in both incongruent and congruent trials by 14±28 ms (p=.002) and 14±25 ms (p=.009), respectively. Elites outperformed youth athletes in their shooting performance (p1000). CONCLUSION: Our findings contradict previous results in conventional shooting and archery sports, as elite biathletes showed no better flanker conflict control than youth. Hence, selective attention, as measured by the Flanker Task, seems not to be a determining factor for biathlon performance. Mindfulness training, which has been shown to improve the attention networks in elite shooters and archers (1), may not be as promising in biathlon. The improvements in RT after the simulated race are in line with the observation that maximum physical exhaustion facilitates information processing speed in the Flanker Task (3), which can be explained by the astrocyte-neuronal lactate-shuttle hypothesis.